The correlation between red cell distribution width, autoimmunity and nail involvement in alopecia areata - Gürel, Gülhan (The European Research Journal, 2019)
Objectives: Alopecia areata is a widespread autoimmune disease that targets hair follicles, and is characterized by nonscarring patches of hair loss. Red cell distribution width (RDW) is a routinely analyzed parameter during complete blood count, and indicates variations in diameters of red blood cells. Elevated RDW levels are associated with high level of inflammation and oxidative stress. In this study, we aimed to demonstrate the correlation between RDW levels, autoimmunity, and nail involvement in alopecia areata. Methods: Medical records of 170 patients who were admitted to our dermatology clinic between May 2016 and May 2017 were retrospectively evaluated. A total of 170 patients with alopecia areata diagnosis were evaluated. Results: The mean age of the patients was 24.61 ± 12.62 years (3-59 years). Sixty patients (35.3%) were female, and 110 patients (64.7%) were male. Twenty-seven patients (15.9%) had nail involvement, and 24 patients (14.1%) had a history of an autoimmune disease. RDW levels were significantly higher in patients with nail involvement and history of an autoimmune disease. Conclusion: RDW can be used as a simple, cheap, and readily available marker of inflammation in patients with alopecia areata.